Sobre a ocorrência de copiapite na orla meso-cenozóica occidental de Portugal - Soares, A. F. (2008)
The occurrence of a copiapite in the Paleogenic (?) formations of Vale Furado (South of S. Pedro de Muel, Portugal) is described, X-ray, DTA and TGA data and a chemical analysis of this mineral are presented.